Digital Lighthouse Platform: Understanding the Misinformation Phenomenon on WhatsApp - Monteiro Filho, José Maria da Silva; de Sá, Ivandro Claudino; da Cunha, Lucas Cabral Carneiro; Barreto, Helena Martins do Rego; Mourão, Pedro Jorge Chaves (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD); 2021: Anais Estendidos do XXXVI Simpósio Brasileiro de Bancos de Dados, 2021)
In the past few years, the large-scale dissemination of misinformation through social media has become a critical issue, harming the trustworthiness of legit information, social stability, democracy and public health. In many developing countries such as Brazil, India, and Mexico, one of the primary sources of misinformation is the messaging application WhatsApp. In February 2020, the Panorama Mobile Time/Opinion Box survey on mobile messaging in Brazil revealed that WhatsApp was installed on 99% of Brazilian smartphones. Among users of the application, 98% said they access it every day or almost every day. In this context, WhatsApp provides an important feature: the public groups. Many of these groups have been used to spread misinformation, especially as part of articulated political or ideological campaigns. Despite this scenario, due to WhatsApp's private messaging nature, few methods were explicitly developed to investigate the misinformation phenomenon on this platform. This tutorial provides an overview of recent developments in monitoring misinformation spreading, automatic misinformation detection, and identifying misinformation spreaders. In addition, we provide an overview of the leading open problems associated with the misinformation phenomenon and briefly examine some of the existing solutions. We hope that our tutorial can help researchers better understand Brazil's misinformation propagation and use data science methods to face this critical phenomenon.